DAMPAK PROGRAM MAKAN BERGIZI GRATIS (MBG) TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA - Muh. Rama Wijaya; Elva Andriani; Nabila Khusnul Hatima; Julia Julia; Arsita Arsita; Yaman La Ndibo (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
The unfastened Nutritious Meal application (MBG) is a strategic authorities initiative aimed at enhancing college students’ dietary fame and supporting instructional pleasant. good enough nutrients performs a essential position in enhancing college students’ bodily health, cognitive development, and emotional balance, which are intently related to mastering motivation and educational fulfillment. This take a look at aims to investigate the impact of the unfastened Nutritious Meal program on college students’ getting to know motivation and academic fulfillment the usage of a literature review technique. relevant country wide and global scholarly articles were systematically reviewed to identify patterns, similarities, and key findings associated to school nutrition programs and mastering outcomes. The effects suggest that the free Nutritious Meal program undoubtedly affects college students’ motivation, attention, school attendance, lecture room engagement, and academic overall performance. these findings suggest that MBG contributes now not most effective to improving college students’ health but also to strengthening getting to know first-class and educational fairness. consequently, the mixing of nutrition applications into educational policy is important for sustainable improvement in student studying effects. ABSTRAK Program Makanan Bergizi Gratis (MBG) adalah inisiatif pemerintah strategis yang bertujuan untuk meningkatkan status gizi siswa dan mendukung kualitas pendidikan. Nutrisi yang cukup memainkan peran penting dalam meningkatkan kesehatan fisik, perkembangan kognitif, dan keseimbangan emosional siswa, yang terkait erat dengan motivasi belajar dan prestasi akademik. Studi ini bertujuan untuk menyelidiki dampak program Makanan Bergizi Gratis terhadap motivasi belajar dan prestasi akademik siswa menggunakan metode tinjauan pustaka. Artikel ilmiah nasional dan internasional yang relevan ditinjau secara sistematis untuk mengidentifikasi pola, kesamaan, dan temuan kunci yang terkait dengan program nutrisi sekolah dan hasil belajar. Hasil penelitian menunjukkan bahwa program Makanan Bergizi Gratis secara signifikan memengaruhi motivasi, perhatian, kehadiran di sekolah, keterlibatan di kelas, dan kinerja akademik siswa. Temuan ini menunjukkan bahwa MBG tidak hanya berkontribusi pada peningkatan kesehatan siswa tetapi juga pada peningkatan kualitas belajar dan kesetaraan akademik. Oleh karena itu, pengintegrasian program nutrisi ke dalam kebijakan pendidikan sangat penting untuk peningkatan berkelanjutan dalam hasil belajar siswa.